The Correlation of Classroom Participation and Students’ English Achievement at Higher Education in Banten - Ezis Japar Sidik; Sutrisno Sadji Evenddy (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
As a lingua franca, English plays an important role in most aspects of human lives, but acquiring fluent English is very challenging particularly for students in English as a foreign language (EFL) context such as Indonesia. The students rarely obtain learning opportunities and language exposures outside but inside classroom context so that maximizing their time in the classroom through their academic engagement is imperative. This study investigated how the students’ engagement in the classroom contributes to their English academic achievement. The study took a survey involving sixty college students from two universities in Banten. The data was analyzed using the Spearman Rank Correlation using the SPSS program. The finding confirmed that the students’ academic participation in the classroom significantly correlates to their English achievement as proven by the value of sig. at 0.001 which was higher than α value at 0.05 (0.00 > 0.05). Moreover, the correlation between the two variables is strong as the value of correlation coefficient equal to .621. This result suggests that teachers need more efforts to encourage their students participating in the classroom.